Improving the Understanding of Maharah Qira'ah Students of MTsN 3 Jombang Using the Question-Answer Relationships Method - Muhammad Afthon Ulin Nuha; Nurul Musyafa’ah (Al-Arabi: Jurnal Bahasa Arab dan Pengajarannya = Al-Arabi: Journal of Teaching Arabic as a Foreign Language, 2022)
Seventh-grade students of MTsN 3 Jombang in learning Arabic are still low in understanding questions related to reading. They have difficulty identifying the main ideas in the reading, have not been able to make conclusions, and have problem retelling in their language. So it can be concluded that the maharah qiraah of grade VII students is still low. The QAR method provides a framework to help students to be able to read by understanding the material, answering questions, and concluding the reading text. The purpose of this study 1) To determine the level of understanding before and after implementing the QAR method at MTsN 3 Jombang. 2) To determine the effectiveness of the QAR method in increasing the maharah qiraah of class VII students at MTsN 3 Jombang. This study uses a quantitative approach with the type of actual experiment. This study used purposive sampling for classes VII-A and VII-B. Data analysis used descriptive research, normality, homogeneity, and hypothesis testing. The results of this study indicate that 1) After the QAR method treatment in the experimental class in learning Arabic, there was a significant increase in post-test scores and an increase in students' ability to conclude the content of the reading, be able to interpret difficult words in the reading text, and be able to explain the values obtained in reading. 2) Based on the results of research and discussion on the effectiveness of using the QAR method in learning Arabic, it can be concluded that, through the results of descriptive analysis for the experimental class, the average pretest score is 66, and the posttest average value for the experimental class is 74. At the same time, the control class has an average score. The average pretest is 58, and the average posttest value for the control class is 62. It can be concluded that the experimental class is superior and has a significant increase compared to the control class.